Break every yoke: religion, justice, and the abolition of prisons - Dubler, Joshua (Oxford University Press, 2020)
Why not prison abolition? -- The political theology of mass incarceration -- The limits of reformist religion -- Prison religion and prison justice -- The spirit of abolition -- Concluding meditations.